Light-induced photoactivation of hypericin affects the energy metabolism of human glioma cells by inhibiting hexokinase bound to mitochondria - MICCOLI, L; BEURDELEY-THOMAS, A; DE PINIEUX, G; SUREAU, F; OUDARD, S; DUTRILLAUX, B; POUPON, M.-F (Cancer research (Chicago, Ill.), 1998)
Glucose-dependent energy required for glioma metabolism depends on hexokinase, which is mainly bound to mitochondria. A decrease in intracellular pH leads to a release of hexokinase-binding, which in turn decreases glucose phosphorylation, ATP content, and cell proliferation. Thus, intracellular pH might be a target for therapy of gliomas, and a search for agents able to modulate intracellular pH was initiated. Hypericin, a natural photosensitizer, displays numerous biological activities when exposed to light. Its mechanism and site of action at the cellular level remain unclear, but it probably acts by a type II oxygen-dependent photosensitization mechanism producing singlet oxygen. Hypericin is also able to induce a photogenerated intracellular pH drop, which could constitute an alternative mechanism of hypericin action. In human glioma cells treated for 1 h with 2.5 microg/ml hypericin, light exposure induced a fall in intracellular pH. In these conditions, mitochondria-bound hexokinase was inhibited in a light- and dose-dependent manner, associated with a decreased ATP content, a decrease of mitochondrial transmembrane potential, and a depletion of intracellular glutathione. Hexokinase protein was effectively released from mitochondria, as measured by an ELISA using a specific anti-hexokinase antibody. In addition to decreased glutathione, a response to oxidative stress was confirmed by the concomitant increase in mRNA expression of gamma-glutamyl cysteine synthetase, which catalyzes the rate-limiting step in overall glutathione biosynthesis, and is subject to feedback regulation by glutathione. Hypericin also induced a dose- and light-dependent inhibition of [3H]thymidine uptake and induced apoptosis, as demonstrated by annexin V-FITC binding and cell morphology. This study confirmed the mitochondria as a primary target of photodynamic action. The multifaceted action of hypericin involves the alteration of mitochondria-bound hexokinase, initiating a cascade of events that converge to alter the energy metabolism of glioma cells and their survival. In view of the complex mechanism of action of hypericin, further exploration is warranted in a perspective of its clinical application as a potential phototoxic agent in the treatment of glioma tumors.